Extent of Service Quality in Commercial Banks in Punjab - Sharma, Siddharth; Verma, Rajesh (Indian Journal of Marketing, 2015)
Commercial banks in India have experienced vital alterations in their system. Liberalization, globalization, and privatization provided banks with freedom, technology, and improved internal systems, which help them to serve their customers better. The purpose of this paper was to measure the extent of service quality in commercial banks in Punjab. The extent of service quality helps in filling up the gap between expected and perceived service quality and gives a wider picture to recognize the needs of the customers. The SERVQUAL multi-item scale was used to measure the extent of service quality in commercial banks in Punjab. The scale consists of five parameters, that is, Tangibility, Reliability, Responsiveness, Assurance, and Empathy. The study conducted a comparative analysis of extent of service quality in private and public sector banks in Punjab. Primary data was collected from 200 top managers of private as well as public sector banks. It was found that among all the five factors of the SERVQUAL model, Responsiveness acted as a dominant factor and had a greater impact on customers' expected level of satisfaction and service quality.